Evolutionary Global Optimization, Manifolds and Applications - Aguiar e Oliveira Junior, Hime.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents powerful techniques for solving global optimization problems on manifolds by means of evolutionary algorithms, and shows in practice how these techniques can be applied to solve real-world problems. It describes recent findings and well-known key facts in general and differential topology, revisiting them all in the context of application to current optimization problems. Special emphasis is put on game theory problems. Here, these problems are reformulated as constrained global optimization tasks and solved with the help of Fuzzy ASA. In addition, more abstract examples, including minimizations of well-known functions, are also included. Although the Fuzzy ASA approach has been chosen as the main optimizing paradigm, the book suggests that other metaheuristic methods could be used as well. Some of them are introduced, together with their advantages and disadvantages. Readers should possess some knowledge of linear algebra, and of basic concepts ofnumerical analysis and probability theory. Many necessary definitions and fundamental results are provided, with the formal mathematical requirements limited to a minimum, while the focus is kept firmly on continuous problems. The book offers a valuable resource for students, researchers and practitioners. It is suitable for university courses on optimization and for self-study. .
Part I Introductory Information -- Part II Global optimization on manifolds -- Part III Further Applications of fuzzy ASA.
Keywords: Computational intelligence; Econometrics; Mathematical optimization; Statistics .; Computational Intelligence; Quantitative Economics; Continuous Optimization; Statistics in Engineering, Physics, Computer Science, Chemistry and Earth Sciences